Volume Transport Variability on the Northern Argentine Continental Shelf from In Situ and Satellite Altimetry Data - Lago, Loreley Selene (2021)
Direct current observations and satellite altimetry data over the northern portion of the Argentine continental shelf are used to produce an 11-month long hourly time series and a 25-year long daily time series of along-shore volume transport, respectively. At time scales longer than 20 days, the temporal variability of the in situ transport is significantly correlated with the transport inferred from satellite altimetry (r = 0.74). The mean in situ along-shore transport is 2.65 ± 0.07 Sv (1 Sv = 106 m3 s−1) to the northeast and presents large variability, with a peak-to-peak range of 16 Sv. The extended satellite transport presents variability at multiple time scales. The annual cycle is the dominant signal, with a maximum during the austral autumn and a minimum during the austral spring. The interannual component of the transport is significantly correlated (r = −0.5) with the Southern Annular Mode (SAM). SAM-induced along-shore wind stress anomalies over the region modulate the cross-shore pressure gradient that, in turn, modulates the along-shore transport variability. This mechanism holds also at synoptic scales, highlighting the dominant role of the wind on the along-shore transport. Satellite altimetry measurements also indicate that the cross-shore pressure gradient generated by the variability of the Malvinas Current affects the along-shore transport only in the outer 30 km of the continental shelf.